TOF : Kunstvlaai3. - Eggermont, Mique; Sandberg Instituut, Amsterdam (Amsterdam : Sandberg Instituut, 1999)
Dekkers, Geert ; Dauder, Patricia ; Gramsma, Bob ; Holden, Lisa ; Guleryuz, Hatice ; Kaptein, Rob ; Janssen, Twan ; Nijburg, Rinke ; Outjers, Mark ; Oki, Dan ; et al.
TOF: Kunstvlaai3, Sandberg Instituut, Amsterdam, 8/05 tm 16/05
kunstcatalogus